Menjawab Tantangan Pendidikan Inklusif: Praktik Differensiasi Pembelajaran Bahasa Arab di Sekolah Islam Berasrama: Menanggapi Tantangan Pendidikan Inklusif: Praktik Diferensiasi dalam Pembelajaran Bahasa Arab di Pesantren - Hasan Syukur; Muhammad Hidayatullah; Amri Yahya; Irfan Aziz; Muhammad Nur Iman (Language Development Center, 2026)
Background: Inclusive education poses challenges for Arabic language teaching in pesantren-based madrasas, where student diversity in abilities and backgrounds requires adaptive learning approaches. Purpose: This study aims to analyze the implementation of differentiated learning in Arabic language instruction as a response to inclusive education challenges in pesantren contexts. Method: This research employed a qualitative case study design conducted at Darul Faqih Senior High School Malang, which integrates the Independent Curriculum with the Islamic Boarding School curriculum. Observation, in-depth interviews, and documentation were used to gather data. The participants included Arabic language teachers and students representing diverse learning profiles. The research instruments consisted of interview guidelines and observation sheets. Thematic analysis was used to identify patterns of differentiated learning practices and their impact on inclusivity. Results and Discussion: Observation was used to gather data. The findings indicate that differentiated learning is implemented through diagnostic assessments, grouping based on readiness and learning styles, peer tutoring, variation in learning methods and media, and intensive mentoring. The pesantren environment also reinforces Arabic language learning through the use of language in daily life and character-building activities. This strategy improves students' language competence, independence, and collaboration while supporting the principle of inclusivity. This research fills a gap by showing that traditional educational institutions such as Islamic boarding schools can effectively implement modern pedagogical approaches to address learning diversity. Conclusions and Implications: Differentiated learning in pesantren based schools successfully bridges modern pedagogy and traditional values, fostering inclusive and character-based Arabic education. Future research should explore scalable models for integrating differentiated instruction into other language and cultural education settings.